THEORETICAL ASPECTS OF LEADERSHIP AND CREATIVITY - Stevanovic, Ana (International Journal of Economic Practice and Policy, 2015)
The paper provides an overview of the theory of leadership which, within the organizational context, can contribute to the development of organizational creativity, as well as employee creativity . First, we observe the most dominant theories of creativity in the organizational context such as the componential theory of creativity and the theory of organizational creativity. Later we examine the theory of leadership within organizations that can increase and have a positive effect on creativity. Among the most important approaches to research of organizational behavior, and leadership theories,are the following : theories of personality traits, behavioral theory of leadership, situational leadership theory and new concepts of leadership. New concepts of leadership include charismatic leadership,  transactional leadership theory and transformational leadership theory. According to the previous research, the latter, i.e. transformational leadership theory,  has a large and significant impact on encouraging creativity within organizations.
Keywords: creativity; LEADERSHIP; theory; organizational context; management; transformational leadership; transactional leadership